Powering a good society. (September 2018) - Knight, Barry
A recent study shows that current methods to reduce poverty are failing. A change of direction is needed, since traditional methods of job creation and social security are unlikely to work in the future. The answer lies not in a set of transactional policies that shift resources but in the development of transformational relationships that shift power. This article will describe the society people want. The research is based on social surveys, focus groups and participative research that include the views, among others, of minorities, migrants, children, community groups and organised groups of poor people in the UK. Findings suggest five principles for a good society: a decent standard of living, a sense of security, freedom to be creative, respectful relationships and a sustainable future for the next generation. The paper examines the role of people and organisations in communities organising from the bottom up to reshape their local economies and to build inclusive communities. This article is based on a five-year research programme by the Webb Memorial Trust asking three questions: What is a good society without poverty? How do we obtain that society? Who does what to implement a good society without poverty?